Hubungan Kecemasan, Motivasi Dan Dukungan Keluarga Terhadap Kunjungan Posyandu Balita Pada Masa Pandemi - Dedek Sutinbuk; Deri Kusmadeni (Citra Delima Scientific journal of Citra Internasional Institute, 2023)
Relationship between mother's anxiety, mother's motivation, and family support to toddlers posyandu visits in pandemi time in the work area of Public Health Center Gerunggang Posyandu is a form of Community Health Based (UKBM) that is managed from, by, for, and with the community with technical support from health workers in the context of achieving NKKBS (Value of happy and prosperous small family), in order to empower the community and provide convenience to the community in obtain basic health services for mothers, infants and children under five. The purpose of this study was to determine the relationship between mother's knowledge, mother's attitude, mother's anxiety, mother's motivation, family support and the role of health workers with visits to Posyandu under five in the working area Gerunggang Public Health Center. This study used a cross-sectional study design using the chi-square test with univariate and bivariate analysis, purposive sampling technique, and data collection using interview techniques through questionnaires. The minimum number of samples in this study amounted to 109 respondents. The results showed that there was a significant relationship between mother's attitude (p=0.043), maternal anxiety (p=0.034), mother's motivation (p=0.029) family support (p=0.036). The most dominant relationship with visits to Posyandu under five was the role of mother's motivation (p = 0.029, POR = 2.569). It is hoped that Health workers will further improve counseling and counseling to families and mothers of toddlers on the importance of visiting toddlers to Posyandu.